Energy and Performance Analysis of Raspberry Pi with Modern Computing Devices - Akshay, S.; Vishnukumar, B.; Mohan, Vimal; S. Anand, M. (International Journal of Engineering and Technology, 2018)
In today’s accessible world, web has turned into a fundamental requirement of everybody. Barring the principal choices of the web, i.e., aquatics and net perusing, we’d like further choices like diversion, on-line video spilling and meeting up and so on. To use entirely unexpected alternatives of the web, very surprising gadgets are offered that changes as far as esteem, figuring force, and show and vitality consumption. Amid this paper, we tend to blessing however entirely unexpected alternatives of the web might be surfed by having one gadget Raspberry Pi. We tend to think about very surprising attributes of Raspberry Pi with in vogue processing gadgets like tablet PC, Smartphones convenient PC and TV. Our outcomes demonstrate that basic registering assignments might be expert in extra vitality practical means. We have a tendency to demonstrate that Raspberry Pi expends less power and may save eminent amount of vitality in routine processing undertakings. Â Â